(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This abstract analyzes the concept of "Dasein" as presented in M. Heidegger’s work, "Being and Time." It examines "Dasein" as the ontological structure of human existence, shedding light on its fundamental characteristics such as being-in-the-world, care, temporality, and being-towards-death. The analysis further emphasizes the significance of "Dasein’s process of self-understanding and its aspiration towards an authentic life, emerging from the depersonalizing influence of "Das Man" (the "They") within the social environment. This concept serves as a crucial theoretical foundation for a deeper understanding of contemporary human existence’s relationship with Being and for examining its place in society and the process of searching for meaning. This study functions as an introduction to Heidegger’s phenomenological ontology, contributing to a profound analysis of the meaning of existence and the essence of human life.